Association of Care in a Medical Home and health care utilization among children with Sickle Cell Disease - Raphael, Jean L. (2013)
OBJECTIVE: Sickle cell disease (SCD) is marked by high utilization of medical services. The aim of this study was to determine whether having a patient-centered medical home (PCMH) is associated with a reduction in emergency care (ED) utilization or hospitalizations among children with scd. METHODS: We collected and analyzed data from parents of 150 children, ages 1 to 17 years, who received care within a large children's hospital. The primary dependent variables were rates of parent-reported ED visits and hospitalizations. The principal independent variable was parent-reported experience with an overall PCMH or its four individual components (regular provider, comprehensive care, family-centered care, and coordinated care). Multivariate negative binomial regression, yielding incident rate ratios (irr), was used for analysis. RESULTS: Children who received comprehensive care had half the rate of ED visits (IRR 0.51, 95% confidence interval, 0.33-0.78) and nearly half the rate of hospitalizations (IRR 0.56, 95% confidence interval, 0.33-0.93) compared to children without comprehensive care. No other component of the PCMH was significantly associated with ED visits or hospitalizations. Children reported to have excellent/very good/good health status had lower odds of ED visits and hospitalizations compared to those reported to be in fair/poor condition. CONCLUSIONS: Children with SCD reported to experience comprehensive care had lower rates of ED encounters and hospitalizations after controlling for demographics and health status. The overall findings highlight that the provision of comprehensive care - having a usual source of care and no problems with referrals - may provide a strategy for improving pediatric SCD care.